Spatio-Temporal Evolution and Driving Mechanism of Coupling Coordination of Pseudo Human Settlements in Central China’s Urban Agglomerations - Shenzhen Tian; Yadan Wang; Xueming Li; Wenmei Wu; Jun Yang; Xueping Cong; Hui Wang (Land, 2024)
The construction of pseudo human settlements in the context of “digital-real integration” in the information age is crucial for the high-quality development of human settlements in the new era. This study aimed to investigate the spatio-temporal evolution of the pseudo human settlements and its mechanism to provide new ideas for scientific breakthroughs in cross-disciplinary fields, such as human settlements, and to provide a strong basis for promoting the overall improvement of the quality of the human settlements in the central China’s urban agglomerations in the new era. Employing the theoretical framework of “three states” in human settlements, this study utilizes big data, including tourism, shopping, work, and socialization, to investigate the dynamic patterns and driving mechanisms of pseudo human settlements within Central China’s urban agglomerations from 2011 to 2021, employing methodologies such as the coupling coordination model, standard deviation ellipse, kernel density, and gray correlation degree. The results show the following: (1) the overall pseudo human settlements in central China’s urban agglomerations exhibit a pattern of “high coupling and low coordination”. (2) The overall coupling degree exhibits a fluctuating upward trend and has been at a high coupling-state level. (3) The degree of coupling coordination has obvious spatial differentiation characteristics, such as the core circle, “tower”, and “two main and one secondary” core structure. (4) The overall level of pseudo human settlements is influenced by the combination of time, space, and the multidimensionality of systems and indicators. This study conducted research on pseudo human settlements to enrich the theory of the human–land interaction relationship in geography and reflect the decision-making needs in the strategy of network power.